1984
DOI: 10.1002/ajh.2830160411
|View full text |Cite
|
Sign up to set email alerts
|

Pancytopenia with hypercellular bone marrow—a possible paraneoplastic syndrome in carcinoma of the lung: A report of three cases

Abstract: Three patients with idiopathic pancytopenia and hypercellular bone marrow who developed carcinoma of the lung within two years of diagnosis are reported. All three patients had macrocytic anemia associated with a megaloblastic marrow in the presence of normal serum vitamin B12 and folic acid levels. Neutropenia with monocytosis, elevated serum muramidase and LAP scores, and increased fetal hemoglobin levels were also found. In all cases Ham's tests were negative with a normal bone marrow karyotype. In all thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Dysplasia of the bone marrow accompanying malignant processes has been documented [9][10][11]. The persistent monocytosis in our pa tient, observed also in other cases of malignant diseases [11,12], supports the etiological role of the malignant tu mor in the development of the myelokathexis.…”
Section: Discussionsupporting
confidence: 85%
“…Dysplasia of the bone marrow accompanying malignant processes has been documented [9][10][11]. The persistent monocytosis in our pa tient, observed also in other cases of malignant diseases [11,12], supports the etiological role of the malignant tu mor in the development of the myelokathexis.…”
Section: Discussionsupporting
confidence: 85%
“…With respect to the development of secondary acute leukemia, age, disease stage, type of cancer, 221 and immunologic status including the postsplenectomy state [222][223][224][225] have all been considered to have a role. In some instances, the development of myelodysplasia or acute leukemia could even be considered a paraneoplastic syndrome 226,227 since there is precedent for the cytokine-driven development of acute leukemia. 228 With respect to polycythemia vera, given the increasing incidence of acute leukemia with age, 5 the mean age of polycythemia vera patients, and the restoration of the polycythemic state with successful remission induction therapy, 220,229,230 the possibility of a chance occurrence cannot be excluded particularly with the simultaneous presence of both disorders.…”
Section: Spontaneous Acute Leukemia: Richter Syndrome Revisitedmentioning
confidence: 99%
“…59 cases of high count (d>5.0 x 10-19) CMML in a total of It has also been suggested that the incidence of second 120 (49.2%) patients, we found only a small number (17/97: malignancies in CMML may be increased (Copplestone et 17 .5%) Reasons for this discrepancy are unclear but may be al., Mufti et al, 1983) and some authors consider that related to sampling methods and diagnostic criteria a picture of CMML may occur as part of a paraneoplastic employed. In our survey, all cases with primary dysplasia syndrome (Haznedar, 1985;Raz et al, 1984; Sans-Sabrafen referred from a wide population area were examined as et al., 1986). Seven of our series of patients had a carcinoma potential 'low count' CMML and, conversely, we reviewed present before the diagnosis of CMML was made and it is all cases of atypical chronic granulocytic leukaemia (CGL) therefore possible that in these cases the picture of dysplasia and myeloproliferative disease as potential 'high count' cases and monocytosis was a result of the carcinoma, rather than and cases were diagnosed as CMML only if they fulfilled the representing the development of a new tumour.…”
Section: Although Cases With Features Of Cmml Have Been Identifiedmentioning
confidence: 99%